Development of E-LKPD Based on Search, Solve, Create, and Share (SSCS) to Empower Critical Thinking Skills in Class X High School Students' Biology Learning - Yulianti, Winda; Ndzani Latifatur Rofi'ah; Eka Vasia Anggis (Universitas Islam Negeri Walisongo Semarang, 2025)
The 21st century is characterized by rapid advancements in science and technology, making critical thinking an essential competency for students. Preliminary research at SMA Negeri 1 Limbangan revealed that 69.44% of students were in the very low category of critical thinking, with an average score of only 20%. This issue is attributed to teacher-centered learning and conventional instructional materials that provide minimal opportunities for analytical activities. This study aims to develop an Electronic Student Worksheet (E-LKPD) based on the Search, Solve, Create, and Share (SSCS) model for biology learning, evaluate the validity of the product, and analyze students’ responses. A Research and Development (R&D) approach using the 4-D model (Define, Design, Develop, Disseminate) was employed, focusing on the Develop stage, involving 36 Grade X students. Expert validation, including material, media, instructional methodology, critical thinking, and biology teachers, showed high validity (average >90%). A small-scale trial revealed positive student responses with an average score of 90.4%, indicating high readability and practicality. The findings demonstrate that the SSCS-based E-LKPD effectively enhances students’ critical thinking, facilitates inquiry-based learning, and bridges the gap between conventional learning materials and 21st-century competency needs. This study underscores the necessity of innovative digital instructional tools that integrate critical thinking models to prepare students for global challenges.